Conversão de plantio homogêneo de Araucaria angustifolia (Bertol.) Kuntze em floresta biodiversa, Capão Bonito, SP - Ramos, Marli (Universidade Federal de São Carlos, 2023)
Biodiverse forests have originated from old homogeneous plantations. In the Araucaria Forest of the National Forest of Capão Bonito - SP, the following were evaluated for adults and juveniles: richness, diversity, evenness, importance value, degree of threat, successional aspects and similarity between adults and juveniles and of this study with nine others from the State of São Paulo. In 65 plots of 10 x 20 m, 1.3 ha, for the adult component – CA (Circumference at breast height – CAP ≥ 15cm), 2,055 individuals, 51 families, 110 genera and 198 species, 1,580.8 individuals.ha-1, 40.3 m2.ha-1 and 53 rare species (one individual), H' = 4.17, J = 0.79. For the juvenile component – CJ (total height ≥ 1 m and CAP < 15 cm), in 5 x 5 m subplots, 425 individuals, 32 families, 67 genera, 111 species and density of 2,698.4 ind.ha-1, H' = 4.16, J = 0.88. Three families stood out in CA and CJ: Myrtaceae, Lauraceae and Fabaceae. There was a predominance of late secondary species 43.7% of the total number of native species (complete binomial), 43.4% in CA and 46.6% in CJ. In importance value, nine out of 10 CA species are non-pioneers. There were six endangered species. There was similarity between CA and CJ, Jaccard = 0.45, Morisita-Horn = 0.73. And dissimilarity of this study with others from the Araucaria Forest in São Paulo State. Still, for the adult component, separating into the reforestations of 1945 (REF45), 1956 (REF56) and 1967 (REF67), was obtained the diameter (DBH, cm), the basal area per hectare (AB, m2.ha-1), the total height (Ht, m) and the density (D, ind.ha-1), in this order: REF45: 14.3; 39.7; 11.3; 1,561; REF56: 13.5; 39.9; 11.5; 1,690 and REF67: 17.3; 44.7; 13.4; 1,561. The diametric distribution, for the three reforestations, presented the “inverted-J” pattern of heterogeneous forests in species and age and the hypsometric distribution registered 46.6% of the total density in the interval between 7.4 and 13.1 m, resembling the natural Araucaria Forest. Araucaria angustifolia stood out in importance value. And the soils were very acidic, with low fertility, high concentration of aluminum, but with high cation exchange capacity, which reduces possible toxic effects to plants, indicating adaptability of the species to soils with nutritional deficiency and acidity.
Conversion of homogeneous planting of Araucaria angustifolia (Bertol.) Kuntze in biodiverse forest, Capão Bonito, SP
Keywords: Biodiversidade; Sucessão florestal; Edafo-estrutura florestal; Biodiversity; Forest succession; Forest edafo-structure; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::QUIMICA DO SOLO; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::CONSERVACAO DE AREAS SILVESTRES